(untitled) (Historia, 2021)
It is now nearly thirty years since Merle Lipton published an article in African Affairs under the title "Debate about South Africa : Neo-Marxists and neo-liberals" (1979) and almost twenty-five years since she published her book Capitalism and apartheid (1985), the main purpose of which was to refute the "revisionists" alleged suggestions that capitalists were either the architects, or major beneficiaries, of segregation and apartheid. It is doubtful whether this "bitter dispute" was ever much more than a storm in a teacup and it is now, if I may mix my metaphors, a very dead horse. It is probably the case that both sides in this argument initially went too far and that what she describes as the "revisionists" secondary position - that capitalists may not have wanted segregation and apartheid, but were quite well able to accommodate themselves to it - is not only a compromise position, but also one that may come as near as possible to that elusive commodity : historical "truth".